Proteomic Analysis Suggests Altered Mitochondrial Metabolic Profile Associated With Diabetic Cardiomyopathy - Gomes, Karina P.; Jadli, Anshul S.; de Almeida, Luiz G. N.; Ballasy, Noura N.; Edalat, Pariya; Shandilya, Ruchita; Young, Daniel; Belke, Darrell; Shearer, Jane; Dufour, Antoine; Patel, Vaibhav B. (Frontiers in Cardiovascular Medicine, 2022)
Diabetic cardiomyopathy (DbCM) occurs independently of cardiovascular diseases or hypertension, leading to heart failure and increased risk for death in diabetic patients. To investigate the molecular mechanisms involved in DbCM, we performed a quantitative proteomic profiling analysis in the left ventricle (LV) of type 2 diabetic mice. Six-month-old C57BL/6J-lepr/lepr (db/db) mice exhibited DbCM associated with diastolic dysfunction and cardiac hypertrophy. Using quantitative shotgun proteomic analysis, we identified 53 differentially expressed proteins in the LVs of db/db mice, majorly associated with the regulation of energy metabolism. The subunits of ATP synthase that form the F1 domain, and Cytochrome c1, a catalytic core subunit of the complex III primarily responsible for electron transfer to Cytochrome c, were upregulated in diabetic LVs. Upregulation of these key proteins may represent an adaptive mechanism by diabetic heart, resulting in increased electron transfer and thereby enhancement of mitochondrial ATP production. Conversely, diabetic LVs also showed a decrease in peptide levels of NADH dehydrogenase 1β subcomplex subunit 11, a subunit of complex I that catalyzes the transfer of electrons to ubiquinone. Moreover, the atypical kinase COQ8A, an essential lipid-soluble electron transporter involved in the biosynthesis of ubiquinone, was also downregulated in diabetic LVs. Our study indicates that despite attempts by hearts from diabetic mice to augment mitochondrial ATP energetics, decreased levels of key components of the electron transport chain may contribute to impaired mitochondrial ATP production. Preserved basal mitochondrial respiration along with the markedly reduced maximal respiratory capacity in the LVs of db/db mice corroborate the association between altered mitochondrial metabolic profile and cardiac dysfunction in DbCM.